Front entrance of Clarendon Terrace, Clarendon St., East Melbourne, 1977, 2 - Sievers, Wolfgang, 1913-2007. (1977)
Illustrates the architecture and exterior design of the Clarendon Terrace, 210 Clarendon Street, East Melbourne, 1977.
Condition: Good.
Title devised by cataloguer based on inscription on reverse.
Part of the collection: Wolfgang Sievers photographic archive.
Sievers number: 4540D.
Also available online
Keywords: Clarendon Terrace (East Melbourne, Vic.) -- Photographs; Architectural photography -- Victoria -- Melbourne -- Photographs